1993
DOI: 10.1007/bf00853223
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of peritoneal dialysis delivery in children

Abstract: We measured urea [weekly urea clearance/total body water (KT/Vurea)] and creatinine (CCr) clearances on 35 occasions in 15 stable chronic peritoneal dialysis patients to determine the feasibility and reproducibility of such measurements in children. In addition, we performed peritoneal equilibration tests (PETs) to characterize our patients' peritoneal membranes and to estimate weekly clearances. We demonstrated that dialysis delivery can be quantified by these standard measurements in children of widely varyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 9 publications
1
15
0
1
Order By: Relevance
“…Twardowski et al first developed the peritoneal equilibration test (PET) to characterize peritoneal transport rates [73]. There have been numerous reports to date on the use of PET in children [65,71,[74][75][76][77][78][79][80]. Warady et al addressed the lack of a standardized process and published pediatric reference data in 1996 from 95 children who underwent a standardized pediatric PET protocol [81].…”
Section: Guideline Xi: Intraperitoneal Volumementioning
confidence: 99%
“…Twardowski et al first developed the peritoneal equilibration test (PET) to characterize peritoneal transport rates [73]. There have been numerous reports to date on the use of PET in children [65,71,[74][75][76][77][78][79][80]. Warady et al addressed the lack of a standardized process and published pediatric reference data in 1996 from 95 children who underwent a standardized pediatric PET protocol [81].…”
Section: Guideline Xi: Intraperitoneal Volumementioning
confidence: 99%
“…4). It is interesting to note that in patients 2, 3, 5 and 6, there was little change in values from 120 min to 240 min, as would be anticipated from previous studies which demonstrate that children tend have more rapid equilibration of solutes [2][3][4]. Representation of mean values for the PETs are shown in Fig.…”
Section: Resultsmentioning
confidence: 52%
“…Depending upon the category into which an individual patient falls, the best dialytic modality for that patient may be selected [1, 2[. Recent data have also shown that the ratios obtained from the standard PET can be used to estimate clearance [4]. However, the D/P ratios that were used to calculate clearance in these patients were obtained at the 4-h time-point.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations